QUALITY OF LIFE ANALYSIS IN DIABETES MELLITUS TYPE 2 PATIENTS USING MONOTHERAPY AND COMBINATION TREATMENT OF MEDICINE - Faridah, Imaniar Noor; Dewintasari, Venty (Indonesian Journal of Pharmacy, 2017)
Treatment of diabetes mellitus (DM) can be vary, using monotherapy or combination therapy, and it depends on the severity of the disease. That variation will give influences to the patient’s clinical condition and also their quality of life (QoL). The objective of this study is to determine the average of QoL’s score in DM patients who use monotherapy and combination therapy of antidiabetic oral in Public Health Center of Kotagede 1 Yogyakarta. This study was conducted in a cross sectional  study. Subjects were people who had an age above 18, got the diagnose of DM type 2, and also consumed of oral antidiabetic monotherapy or combination. The measurement of QoL is using a DQLCTQ questionnaire in Bahasa Indonesia. Analysis statistic with independent sample T-test was used to determine the differences between QoL in patients who use monotherapy and combination. Subjects who met the inclusion criteria are 52 patients. About  82.70% (43 patients) of the patients used combination and the other (9 patients) used monotherapy. The average of QoL in monotherapy patients (78.95±11.36) was higher than in combination therapy’s (75.18±10.57). Result of the analysis statistic showed that there is no significant differences (p0.095) of QoL between monotherapy and combination therapy patients.